Buku Katan: satu kajian awal leksikografi Melayu (Jurnal Bahasa, 2022)
This article discusses several aspects of lexicography in a monolin-gual Malay language dictionary, Buku Katan. Published in 1936 by Pakatan Bahasa Melayu Persuratan Buku (P.B.M.P.B.) Diraja Johor, this dictionary was arranged by Hj. Mohd. Said bin Haji Sulaiman. The aspects discussed include the form and type of entries as well as the method of explaining meaning. This Buku Katan is compared with Kamus Dewan and Kamus Umum Bahasa Indonesia. Buku Katan con-tains virtually all the lexicography aspects of a monolingual Malay language dictionary. Besides, this article contains a background of Pakatan Bahasa Melayu Persuratan Buku (P.B.M.P.B.) Diraja Johor and Hj. Mohd. Said bin Haji Sulaiman.